Pengaruh Titik Akupresur Ht7 Terhadap Insomnia Pada Ibu Nifas Di Puskesmas Lurah Kabupaten Cirebon - Juariah, Siti; Diyanti, Lies (Indonesia Berdaya, 2024)
Insomnia is a common issue in postpartum mothers, often resulting from hormonal changes and stress, and it can negatively impact both maternal health and infant care. Due to concerns about the side effects of pharmacological treatments, non-pharmacological alternatives like acupressure are gaining attention. This study explores the effectiveness of HT7 (Shenmen) acupressure, a technique rooted in traditional Chinese medicine, in alleviating insomnia among postpartum mothers at the Cirebon Regency Village Health Center. Employing a Pre-Experimental design, this quantitative research included 35 postpartum mothers who experienced insomnia between May and July 2024, selected through total sampling. Data analysis involved both univariate and bivariate methods, with statistical testing conducted via the Paired Samples Test using SPSS. The results revealed a significant improvement in sleep quality post-intervention (p = 0.000, α = 0.05), indicating that HT7 acupressure effectively reduces insomnia in postpartum women. The study provides valuable insights for mothers by introducing HT7 acupressure as a safe, natural, and low-risk alternative for managing insomnia and stress, potentially enhancing their overall postpartum well-being.